Management of Energy and Manufacturing System - Xia, Tangbin; Pan, Ershun; Wang, Rongxi; Li, Yupeng; Gu, Xi (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on recent advancements, technical challenges, and novel design methodologies for the energy manufacturing system, including energy management, green manufacturing, sustainable manufacturing, energy saving in manufacturing systems, the operation and maintenance of power generation, prognostics and health management of power systems, and so on. With the increasing attention paid to sustainable development around the world, improving energy efficiency and applying effective means of energy saving have gradually received worldwide attention. As the largest energy consumers, manufacturing industries also inevitably face pressures on energy optimization evolution from both governments and competitors. The rational optimization of energy consumption in industrial operation activities can significantly improve the sustainability level of an entire company.